The influence of textbooks on teachers' knowledge of chemical bonding representations relative to students' difficulties understanding. Issue 2 (3rd April 2017) - Bergqvist, Anna; Chang Rundgren, Shu-Nu
Abstract: Background: Textbooks are integral tools for teachers' lessons. Several researchers observed that school teachers rely heavily on textbooks as informational sources when planning lessons. Moreover, textbooks are an important resource for developing students' knowledge as they contain various representations that influence students' learning. However, several studies report that students have difficulties understanding models in general, and chemical bonding models in particular, and that students' difficulties understanding chemical bonding are partly due to the way it is taught by teachers and presented in textbooks. Purpose: This article aims to delineate the influence of textbooks on teachers' selection and use of representations when teaching chemical bonding models and to show how this might cause students' difficulties understanding. Sample: Ten chemistry teachers from seven upper secondary schools located in Central Sweden volunteered to participate in this study. Design and methods: Data from multiple sources were collected and analysed, including interviews with the 10 upper secondary school teachers, the teachers' lesson plans, and the contents of the textbooks used by the teachers. Results: The results revealed strong coherence between how chemical bonding models are presented in textbooks and by teachers, and thus depict that textbooks influence teachers' selection and use of representations for their lessons. As discussed in the literature review, several of the selected representations were associated with alternative conceptions of, and difficulties understanding, chemical bonding among students. Conclusions: The study highlights the need for filling the gap between research and teaching practices, focusing particularly on how representations of chemical bonding can lead to students' difficulties understanding. The gap may be filled by developing teachers' pedagogical content knowledge regarding chemical bonding and scientific models in general.